A Qualitative Study of the Ionospheric Weak Response to Super Geomagnetic Storms - Haimeng Li (Atmosphere, 2020)
The ionospheric response to a geomagnetic storm is a geophysical process. Although strong geomagnetic storms input more energy into the Earth’s upper atmosphere, the ionospheric response often does not reflect the same level of variation as the geomagnetic storm, and the response may be weak during a very strong storm. However, the estimated ionospheric response to geomagnetic activity also varies with extraction method. Here, two different methods—the spectral whitening method (SWM) and the monthly median method (MMM)—are used to verify whether the apparent weak ionospheric response is an artifact of the processing method. The weak ionospheric response is found with both methods, which suggests it is a real ionospheric phenomenon. The statistical characteristics of the regional and global ionospheric weak response to a super geomagnetic storm (SGS) and to an SGS with a preceding storm event (SGS-PRE) are investigated and compared. The results show that the regional ionospheric weak response to an SGS is more prevalent at middle latitudes than those at low and high latitudes. The global ionospheric weak response occurs more frequently under high solar activity and has a strong correlation with SGS-PRE, which suggests that the effect of a storm on the ionosphere can be influenced by its preconditioning, especially when there is an earlier storm and the time interval between the two storms is short. In fact, an ionospheric long-lasting disturbance may be an important reason for the ionospheric weak response caused by the SGS-PRE.